2012
DOI: 10.4103/0974-9233.92121
|View full text |Cite
|
Sign up to set email alerts
|

Short-term visual outcomes of Boston keratoprosthesis type I in Saudi Arabia

Abstract: Purpose:To evaluate the visual outcomes, complications and retention of threadless type I Boston keratoprosthesis (KPro) in Saudi Arabia.Materials and Methods:Retrospective analysis of four eyes of four patients (one female and three males; age range: 48 to 72 years) who underwent Boston type I threadless KPro implantation between January and December 2009.Results:In the median follow-up of 11 months (range 6 to 14 months), visual outcomes were satisfactory. Preoperative diagnosis included two patients of post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Even in the studies reporting larger dataset (136–300 eyes), retention rate of 93–95% is obtained 31,38 . Case series from Saudi Arabia and Jordan have also reported good retention rates (75–100%) 5,15,42 ; it is important to note that despite the arid climate of this region, which contributes to the ocular surface dryness, the retention rate reported in this study is consistent with the reports from other parts of the world.…”
Section: Clinical Outcomessupporting
confidence: 88%
See 3 more Smart Citations
“…Even in the studies reporting larger dataset (136–300 eyes), retention rate of 93–95% is obtained 31,38 . Case series from Saudi Arabia and Jordan have also reported good retention rates (75–100%) 5,15,42 ; it is important to note that despite the arid climate of this region, which contributes to the ocular surface dryness, the retention rate reported in this study is consistent with the reports from other parts of the world.…”
Section: Clinical Outcomessupporting
confidence: 88%
“…While several studies reported achieving CDVA of 20/50 or better in at least some of the eyes 4 papers reported achieving CDVA of 20/50 or better in 43–60% of their dataset 10,11,17,41 . Visual acuity in case series from arid climatic conditions of Saudi Arabia and Jordan also reported good visual outcomes with 65–100% of the eyes achieving CDVA of 20/200 or better and 0–25% of the eyes achieving visual acuity of 20/50 or better 5,15,42 which are comparable to those from the US (with 20–81% of the eyes achieving CDVA of 20/200 or better and 0–48% of the eyes achieving CDVA of 20/50 or better).…”
Section: Clinical Outcomesmentioning
confidence: 84%
See 2 more Smart Citations
“…The Boston Type 1 keratoprosthesis (KPro), developed at the Massachusetts Eye and Ear Infirmary and approved by the US Food and Drug Administration (1993), is currently the most commonly used keratoprosthesis worldwide [ 4 ] and is used in cases at high risk for penetrating keratoplasty failure [ 5 ]. It has been successfully used to restore vision in cases of chronic corneal disease and graft failure, including corneal alkali burn [ 6 ]. However, despite multiple advances and improvements in prognosis of patients following KPro surgery, several challenges remain.…”
Section: Introductionmentioning
confidence: 99%